STRATEGIC CHALLENGES FOR SUCCESSFUL PROJECT MANAGEMENT IN THE ERA OF COVID-19 ENDEMIC - Farkhanda Naheed; Lamya AlMulla (INTERNATIONAL JOURNAL OF INNOVATION AND INDUSTRIAL REVOLUTION (IJIREV), 2024)
In project management, strategic challenges are likely to be issues or contentions that can have a significant impact on project success. Often project success depends upon how timely and effective strategic implementations were undertaken. Nowadays, Project-based organization cultures are observing a seemingly ever-increasing pace of change and evolving with emerging new technologies. Digital technologies are impacting the dynamics of workplaces by rapidly changing competitive thinking amongst employees including their horizontal and vertical collaborations. After the recent unprecedented times during Covid 19 pandemic, the working methodologies to accommodate remote work cultures have been inculcated into the organizations. This has led to change management, accountability, and productivity determination as a more stern challenge for strategic developments. Additionally, keeping the team focussed and strategically aligned with the organizational mission and vision has become a vital project management aspect. The objective of this article is to explain the strategic challenges faced by project management in strategy implementation in project-based organizations and the possible solutions to the challenges. The ways of succeeding with these challenges effectively are to put more consideration on strategy implementation and develop new strategies to meet with future technology advancements. Moreover, Management should articulate their strategy of how to improve employee capabilities and skills in certain job positions coupled with new technology, which can enhance behavioural strategies for employees. The study will contribute further on new knowledge to the existing body of knowledge on strategy implementation challenges faced by Project management. The study also established that employees’ resistance to change and lack of skills to some extent affected the implementation of strategies within the organizations. However, practicing proper change management in the organization can minimize the resistance. The knowledge gained through this research will thus be useful in improving the overall performance of Projects.